Assessment of Hearing Loss in 2-years Follow up study of Neonates with Congenital Cytomegalovirus Infection - Noorbakhsh, Samileh; Joghataei, Mohammad Taghi; Farhadi, Mohammad; Haghighi, Faezeh; Emamjome, Hesamodin; Haghighi Hasanabad, Morteza (Iranian Journal of Child Neurology, 2022)
Objective: Congenital CMV infection constitutes the main cause of sensory neural hearing loss (SNHL) worldwide. The rate of CMV induced SNHL is not well documented in developing countries like Iran. Therefore, this prospective follow up study was aimed to evaluate this rate among neonates with congenital CMV infection. Materials & Methods: Infants with congenital CMV infection who were admitted to Neonatal Intensive Care Units and infected infants who were identified in 2 other prospective screening studies in our region were enrolled. Audiological follow up was performed for all the cases. Antiviral therapy was administered for the newborns in case of having severe symptoms. Results: A total of 22 infants with congenital CMV infection were entered into the study, of which, 8 and 14 had symptomatic and asymptomatic congenital CMV infection, respectively. In total, 3 of 22 infants had SNHL (13.6%; 95% CI: 2.8-39.8), 2 of 8 with symptomatic cCMV infection (25.0%; 95% CI: 3-90) and 1 of 14 with asymptomatic cCMV infection (7.1%; 95% CI: 0.1-39). No association was found between SNHL and risk factors related to CMV in newborns. In conclusion, the findings of this study revealed that the rate of congenital CMV induced SNHL is high among neonates how born in our region. Severe sequelae of congenital CMV infection indicate the need for screening for CMV infection at birth to reduce the risk of CMV complications and the financial load of treatment imposed on health care and treatment systems in the country.